2000
DOI: 10.1524/zpch.2000.214.11.1439
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Factorization of Molecular Potential Surfaces II. Internal Rotors

Abstract: Scaling models for the polyatomic potential energy surface occupy a ground intermediate between ab initio surfaces and random matrix models. They are useful for the study of vibrational energy redistribution (IVR) in large molecules, and have been shown to reproduce many features of more accurate spectroscopically fitted or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…3,11 Moreover, there is evidence for strong coupling between the three CH fundamentals and the six HCH bend combinations. 17 The spectral region above 5000 cm Ϫ1 contains a large number of vibrational bands that may provide insights into the couplings between the various vibrational modes in methanol. 17 The spectral region above 5000 cm Ϫ1 contains a large number of vibrational bands that may provide insights into the couplings between the various vibrational modes in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…3,11 Moreover, there is evidence for strong coupling between the three CH fundamentals and the six HCH bend combinations. 17 The spectral region above 5000 cm Ϫ1 contains a large number of vibrational bands that may provide insights into the couplings between the various vibrational modes in methanol. 17 The spectral region above 5000 cm Ϫ1 contains a large number of vibrational bands that may provide insights into the couplings between the various vibrational modes in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Their model calculations were compared to ab initio results on several small molecules. Pearman and Gruebele [10] extended this approach to internal rotor molecules including methanol and hydrogen peroxide and found that the IVR coupling matrix elements fell off less rapidly with coupling order than is typical of rigid molecules. The coupling order is the total number of vibrational quanta created or destroyed when one vibrational state is converted to another.…”
Section: Ivr As a Non-adiabatic Effectmentioning
confidence: 99%
“…LA internal rotation has been shown to accelerate intramolecular vibrational redistribution (IVR) between the LA vibration and the SA vibrations with amplitude on nearby nuclei [5][6][7][8][9]. Pearman and Gruebele [10] have shown that when internal rotation is involved, the scaling behavior of the coupling matrix elements results in a slower fall-off of the coupling strength with coupling order than if only SA vibrations were involved. The result is a larger contribution from direct high-order coupling and, in appropriate circumstances, faster IVR [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…State-selected IRLAPS spectra of methanol have shown that IVR occurs on multiple timescales [12][13][14][15]. In their studies of the scaling of IVR coupling matrix elements, Pearman and Gruebele [16] have used methanol as a case study to demonstrate how torsionvibration coupling can lead to enhanced IVR.…”
Section: Introductionmentioning
confidence: 99%